ILORIN EMIRATE TYPE OF ADMINISTRATION IN ISINLAND 1836-1947: A HISTORICAL ANALYSIS - ADOLARIN TUNDE AARON (International Studies Journal)
Isinland people are among the perceived ‘minor’ ethnic groups in Kwara State, Nigeria; whose history is best described as forgotten, with its peculiar administrative organizational structure. This Pre[1]Ilorin Emirate type of administration of Isinland was distorted both in organization and direction with the arrival of Ilorin Emirate political agents into Isinland as heads of administration.The objective of this study is to criticallyinvestigate Ilorin Emirate type of administration in Isinland 1836-1947 as typical example of Ilorin Emirate administration in the non-metropolitan center of the Emirate.The research methodology explored was historical.The primary sources comprised oral interview across prominent individuals of Isinland and at Ajia Opelle’s compound of Ilorin. The interview purposely included Obas such as Oba Solomon OlugbengaOloyede(Olusin of Isanlu-Isin), and Oba Adewuyi David (Allaa of Alla-Isin).While the secondary materials firm research institutes like National Archives Kaduna and other libraries were used. Data collected were qualitatively and quantitatively analyzed using descriptive analysis and the finding showed certain gap, which the existing scholarly attention did not cover. The study odbserved this gap and bridge it. The study concluded that Ilorin type of Administration in Isinland could best be described as hijacking of powers and roles of Isinland traditional rulers; which led to prolong agitationagainst the unrepresentative and undemocratic nature of Ilorin Emirate type of administration in Isinland which culminated in to the withdrawer of the last Ajia from Isinland in 1947.